A STUDY OF THE IMPLICATIONS OF THE GENERATION GAP FOR SOCIAL CHANGE - Ramprit Kumar Keshri (International Journal of Multidisciplinary Research and Studies, 2021)
Generations difference have been noted by Furlong (2016), where he emphasised that this generation difference become more apparent when youth transits into adulthood. As per Furlong some of this gap is natural and others are done by deliberate one and can be seen clearly in gathering as in the market, the clubs, the coffee shops and the activity centre. The sociological theory of a generation gap first came to light in the 1960s, when the younger generation, now known as the baby boomers, shown to have a large gap with their parents‟ values and views in life, Govitvatana (2001). Since then, many studies have shown that physical isolation usually combines the mental isolation between the generations, i.e. usually you would find little interaction or even barriers of interaction across the ages. This isolation used to be clear if the differences in ages of about one decade or more, but today, even if the age difference is less than three years, we would notice this physical isolation. Actually, now the barriers are becoming so difficult that rarely you would see that this chain could be broken. Synthesis of the generational gap literature review shows there are different types of perceptions about the extent of the gap. One type of research sees that the gap between the generations is too deep. Other, type of research sees that there is no big gap between the generations today and what is experienced is only part of the norms of any other cycle of generation. The other literature shows there are selective gaps between the generations. Hence, we can see there is research that is pessimistic about the generational gap, and other research that is optimistic about the generational gap. Certain studies show that generational gap is the cause of identity crisis and the faded role of the common ties that were influenced by the religion, or the school, or the community. Buheji (2018b), Mannheim (1952).